A systematic bibliometric review of the strategic entrepreneurship domain. Issue 6 (18th October 2021) - Thomas, Gareth H.; Douglas, Evan J.; Yamada, Jin-Ichiro; Senyard, Julienne
Abstract : Purpose: The strategic entrepreneurship (SE) literature exists at the intersection of the strategy and entrepreneurship literatures and has grown rapidly over the past two decades. This study aims to document the proliferation of research papers and identifies the major thematic clusters of topics and other summary information for the SE research domain. Design/methodology/approach: This is a systematic bibliometric review of 586 articles published over the period 2009–2019 in 143 journals. The inductive quantitative assessment of these articles uses meta-data driven techniques that prioritize reproducibility and rigor in the process of literature analysis. Findings: This study identifies six main themes in the strategic literature, namely, Sustainable Competitive Advantage; Knowledge Management; Ecosystems; Strategy; Entrepreneurialism; and Organization and Management. It also reports data on a variety of issues including research techniques, country of data, co-author count and trends and differences between journals based on their journal impact factors and calls for more research in key areas. Originality/value: An innovative original analytical tool was developed to facilitate the analysis of research papers in this growing field. This online tool allows multiple tags to be attached to each paper by multiple authors working simultaneously to identify keywords and other aspects that were subsequently used to identify six main thematic areas within the SE literature. This paper highlights emerging research trends and identifies gaps in the literature that provide opportunities for further research in this field.